Monocyte distribution width as part of a broad pragmatic sepsis screen in the emergency department. Issue 2 (28th February 2022) - Malinovska, Alexandra; Hinson, Jeremiah S.; Badaki‐Makun, Oluwakemi; Hernried, Benjamin; Smith, Aria; Debraine, Arnaud; Toerper, Matthew; Rothman, Richard E.; Kickler, Thomas; Levin, Scott
Abstract: Study Objective: Enhancement of a routine complete blood count (CBC) for detection of sepsis in the emergency department (ED) has pragmatic utility for early management. This study evaluated the performance of monocyte distribution width (MDW) alone and in combination with other routine CBC parameters as a screen for sepsis and septic shock in ED patients. Methods: A prospective cohort analysis of adult patients with a CBC collected at an urban ED from January 2020 through July 2021. The performance of MDW, white blood count (WBC) count, and neutrophil‐to‐lymphocyte‐ratio (NLR) to detect sepsis and septic shock (Sepsis‐3 Criteria) was evaluated using diagnostic performance measures. Results: The cohort included 7952 ED patients, with 180 meeting criteria for sepsis; 43 with septic shock and 137 without shock. MDW was highest for patients with septic shock (median 24.8 U, interquartile range [IQR] 22.0–28.1) and trended downward for patients with sepsis without shock (23.9 U, IQR 20.2–26.8), infection (20.4 U, IQR 18.2–23.3), then controls (18.6 U, IQR 17.1–20.4). In isolation, MDW detected sepsis and septic shock with an area under the receiver operator characteristic curve (AUC) of 0.80 (95% confidence interval [CI] 0.77–0.84) and 0.85 (95% CI 0.80–0 .91), respectively. Optimal performance was achieved in combination with WBC count and NLR for detection of sepsis (AUC 0.86, 95% CI 0.83–0.89) and septic shock (0.86, 95% CI 0.80–0.92). Conclusion: A CBC differential panel that includes MDW demonstrated strong performance characteristics in a broad ED population suggesting pragmatic value as a rapid screen for sepsis and septic shock.